Multi-criteria decision support analysis for sustainable water treatment techniques during tunnel construction - Cuellar Rodriguez, Daniel Andres; Kjällström, Filip (My University, 2024)
Urbanization and construction projects, including tunneling activities, contribute substantially to water quality degradation worldwide. Consequently, there is an increasing need for new measures to address water quality concerns, particularly within the European Union, where there is more acknowledgement about this need. In cities like Gothenburg, escalating traffic volumes and limited road network space drive a surge in tunneling projects, potentially threatening aquatic environments. The construction phase of tunnels produces wastewater that contains pollutants coming from the construction site; this water needs to be treated before it is released into water bodies or stormwater systems. However, budgeting for water treatment proves challenging due to fluctuating costs and dynamic construction site activities. This research explores alternative solutions for wastewater treatment during tunnel construction, considering ecological, monetary, and site-specific perspectives. The study comprehensively evaluates and compares treatment alternatives using a Multi-Criteria Decision Analysis (MCDA) approach. By investigating existing treatment facilities and innovative techniques in the Vasastan tunnel at Västlänken Station Haga, Gothenburg, the research aims to identify the most sustainable and suitable solution for treating polluted tunneling wastewater. After the project was conducted, it was found that the tunneling wastewater in the case study had multiple pollutants and contaminants that had to be removed. It was also found that there are multiple techniques to accomplish the separation of pollutants from the tunneling wastewater; and there is not such a thing as a “perfect” or ideal treatment for the case study. Combining different techniques and good sedimentation are key to accomplishing a proper treatment of tunneling wastewater. The findings contribute to the design and implementation of necessary improvements in wastewater treatment systems, promoting environmentally friendly and cost-effective practices. Through thorough examination and evaluation, the study underscores the importance of addressing water treatment challenges to ensure sustainable development.
Keywords: water quality; tunnel construction; wastewater treatment; Multi-Criteria Decision Analysis (MCDA); sustainable development